عقیدۂ ذات و صفاتِ باری تعالیٰ: امام غزالى کے افکار اور ان كى عصرى اہمیت (Al-Qamar, 2020)
Doctrine of Allah Almighty and His attributes is the most important creed in Islam. This article discusses al-Ghazālī’s thoughts on the subject and highlights their contemporary significance.  It shows that al-Ghazālī has very comprehensively elaborated the Islamic creed on Allah Almighty and His attributes. In the light of al-Ghazālī’s ideas special attention needs to be paid to the reform of beliefs on the subject referred. It suggests that contemporary scholars must reform the distortions in the Muslims beliefs by adopting al-Ghazālī’s methodology about the reformation of the distorted beliefs regarding Allah and His attributes. This is the way for the present day Muslim scholars to play their effective role in curbing the growing ideology of atheism.
Keywords: Doctrine; Allah and His attributes; Al-Ghazālī